Physical Fitness Is Correlated with Quality of Life among Elderly Gymnastics Club from Haji General Hospital Surabaya, Indonesia - Hasan Hasan; Rita Vivera Pane (Althea Medical Journal, 2022)
Background: Indonesia is the fourth most populated country, of whom 10.8% are elderly people. The quality of life (QOL), which includes physical health, psychological health, social relationships, and the environment, is crucial as physical fitness may reflect the ability to perform daily activities without significant fatigue. The objective of this study was to explore the correlation of physical fitness with the QOL among the elderly.Methods: This was an analytic observational study with a cross-sectional approach, including members of the elderly gymnastics club of the Haji General Hospital Surabaya. The physical fitness value was measured based on VO2max using a 6-minute walk test (6MWT). The VO2max (0.03 x mileage(m) + 3.98 cc/kilogram body weight/minute) was categorized into poor, moderate, and good. The QOL was assessed with WHOQOL-100 and grouped into poor, moderate, and good QOL. Data were analyzed by the Spearman correlation test.Results: In total, 33 elderly were recruited, with an average age was 67.85±6.11 years (range 60–78), mean height was 1.49±0.09 m, mean weight was 57.65±10.53 kg, and mean BMI was 24.92±3.69. The mean VO2max was 16.96±2.37, and the QOL was 64.61±6.82 mL/kg/minute. The 6MWT resulted in the physical fitness of poor (15%; n=5), moderate (36%; n12), and good (48%; n16). The WHOQOL assessment showed moderate (30%; n=10) and good (61%; n=23) QOL. Spearman correlation test results showed a correlation between physical fitness and the QOL (coefficient 0.356 and p= 0.042).Conclusions: There is a correlation between physical fitness and QOL among the elderly, suggesting that increasing physical fitness among the elderly, adjusted to their physical health condition, is important to get a good quality of life.